Organizações da sociedade civil: entre a solidariedade libertária e a liberal - Santos, Luís Miguel Luzio dos (2007)
This study focused on the discussion of the theme solidarity, under distinct perspectives- namely the liberal and the libertarian proposal. Having solidarity as the aim of the research, ways of expressing such reality have been sought, which led to the universe of the Civil Society Organization in its various expressions and realities. The study was initially carried out along with the Civil Society Organization of Londrina Paraná, which added up to a total of 162 entities studied in order to identify their main characteristics and profile. This has allowed to the creation of a reality like map that comprises the universe of the Civil Society Organization of the city. Later, four entities were selected to represent the diversity of initiatives, in which qualitative elements that were not included in the initial quantitative research were then deeply analyzed. The major directors of those organizations were interviewed to identify and analyze different perspectives. The qualitative investigation was guided by an interview script based on the objectives and issues of the research. The analyses showed important interpretative elements and mainly indicated the diversity of positioning that constitutes the universe of these entities in the city of Londrina, which opposes to the simplistic view of a phenomenon dominated by cohesion and uniformity of interests and actions. The wide divergences identified, plus the diversity of purposes and of world and society view that pervade the different organizations researched, functioned as the basis to choose the topic of this study, distinguished by libertarian and liberal solidarity